2001
DOI: 10.1139/cjz-79-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating snowshoe hare population density from pellet plots: a further evaluation

Abstract: We counted fecal pellets of snowshoe hares (Lepus americanus) once a year in 10 areas in the southwestern Yukon from 1987 to 1996. Pellets in eighty 0.155-m 2 quadrats were counted and cleared each June on all areas, and we correlated these counts with estimates of absolute hare density obtained by intensive mark-recapture methods in the same areas. There is a strong relationship between pellet counts and population density (r = 0.76), and we present a predictive log-log regression to quantify this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(96 citation statements)
references
References 6 publications
2
89
3
2
Order By: Relevance
“…These pellet counts were on uncleared plots and provided our metric of snowshoe hare occupancy (≥1 pellet) and intensity of use (i.e., mean number of pellets/subplot). Many studies have confirmed the positive relationship between snowshoe hare density and pellet counts (e.g., Berg & Gese, ; Krebs et al., ; Krebs, Boonstra et al., ; Mills et al., ; Murray, Ellsworth, & Zack, ); thus, it was conservative and appropriate to use pellets as a measure of intensity of use. We visited our sampling locations only once; therefore, we did not estimate detection probabilities for occupancy (sensu MacKenzie et al., ).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…These pellet counts were on uncleared plots and provided our metric of snowshoe hare occupancy (≥1 pellet) and intensity of use (i.e., mean number of pellets/subplot). Many studies have confirmed the positive relationship between snowshoe hare density and pellet counts (e.g., Berg & Gese, ; Krebs et al., ; Krebs, Boonstra et al., ; Mills et al., ; Murray, Ellsworth, & Zack, ); thus, it was conservative and appropriate to use pellets as a measure of intensity of use. We visited our sampling locations only once; therefore, we did not estimate detection probabilities for occupancy (sensu MacKenzie et al., ).…”
Section: Methodsmentioning
confidence: 96%
“…We sampled snowshoe hares by enumerating snowshoe hare pellets within five 5.1 × 305 cm subplots (Krebs, Gilbert, Boutin, & Boonstra, ; Krebs, Boonstra et al., ) placed at plot center and the four edges of our 20 × 20 m plot. These pellet counts were on uncleared plots and provided our metric of snowshoe hare occupancy (≥1 pellet) and intensity of use (i.e., mean number of pellets/subplot).…”
Section: Methodsmentioning
confidence: 99%
“…Such abundance indices are widely used for hares (Krebs et al 2001;Murray et al 2002) and more recently for grouse (Potvin et al 2001;Huggard 2003). Such abundance indices are widely used for hares (Krebs et al 2001;Murray et al 2002) and more recently for grouse (Potvin et al 2001;Huggard 2003).…”
Section: Estimation Of Species Relative Abundancesmentioning
confidence: 99%
“…The relative abundance of pellets found within each experimental site is proportional to hare population density and was measured by means of pellet counts (Krebs et al 2001). Systematic pellet counting was achieved by placing, in the center of each experimental site, 30 microplots of 4 m 2 each, along a 500 m equilateral triangle transect, at 50 m intervals.…”
Section: Biological Analysismentioning
confidence: 99%